Effects of polypeptide conformation and surface bonding on static secondary ion mass spectra - Worley, C.G (Archīum Ateneo, 1996)
Abstract For the first time, the α‐helical homopolypeptide poly(γ‐benzyl‐L‐glutamate) (PBLG) was synthesized by solid‐phase methods. A 10 residue PBLG sample (10‐mer) was prepared which exhibited a β‐sheet configuration, and a 15 repeat unit PBLG sample (15‐mer) was made which displayed partial α‐helical character. Solvent‐cast thin films of these peptides were deposited on both gold and silver and analyzed by time‐of‐flight static secondary ion mass spectrometry (ToF‐SSIMS). The PBLG 10‐mer spectra consisted of a strong molecular ion (cationized with Na or Ag) and less‐pronounced fragments spaced by the benzyl glutamate mass ( n ‐mers) attributed to SSIMS fragmentation. Contrary to this, the PBLG 15‐mer did not provide an intact molecular ion, and only low‐mass n ‐mer species were observed. These n ‐mers are believed to be a product of SSIMS‐induced molecular fragmentation that is enhanced by the peptide α‐helical conformation. A disulfide moiety (SS) was also coupled to the 10‐mer and 15‐mer N‐termini (10‐merSS and 15‐merSS) to provide a functional group for self‐assembly on gold. Molecular ions were observed from solvent‐cast films of these samples, verifying the presence of the SS cap. However, self‐assembled monolayers of these peptides on gold generated weak SSIMS signals which primarily reflect the strong binding of the SS group to the substrate.